Anthelmintic potential of andrographis paniculate ethanolic leaf extract in caenorhabditis elegans - Rivera, Ivy D., Salandaan, Leora M., Sy, Alvin Gerald P., Villa, Raphael T. 4 0 16; 5
ABSTRACT: Helminthiasis remains a major health concern globally and in the Philippines despite the current mass drug administration program against it. Andrographis paniculata, a plant widely available in the Philippines, received massive attention due to its potent bioactive compounds that exhibit anti-inflammatory and antibacterial properties. However, the mechanisms involved in its anthelmintic potential remain elusive. This study, Anthelmintic Potential of Andrographis paniculata Ethanolic Leaf Extract in Caenorhabditis elegans, investigated the anthelmintic potential of A. paniculata ethanolic leaf extract (APELE) on the eggs, larvae, and adults in Caenorhabditis elegans. It employed an in vivo approach to determine the effects of varying APELE concentrations on the mortality, egg viability, and motility in C. elegans through three assays: Egg Hatch Inhibition, Larva Motility Inhibition, and Adult Motility Inhibition. The results showed that the anthelmintic potential of APELE in terms of egg hatch and larval motility inhibition was highest at 20 mg/mL treatment concentration. In comparison, adult motility inhibition was highest at 10 mg/mL treatment concentration. Statistical analysis showed no significant differences in the anthelmintic activity between 10 mg/mL compared to 20 mg/mL in terms of egg hatch inhibition and larval motility and mortality. While for adult, it showed significant differences in the anthelmintic activity of 20 mg/mL and 40 mg/mL compared to 50 mg/mL, but no significant differences among other concentrations. Lastly, both the most effective concentrations (10 mg/mL and 20 mg/mL) were found to have significant differences compared to the positive control.
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2